Implementation of Patient Safety Management to Improve the Quality of Health Services at Patut Patuh Patju Hospital (Journal of Social And Education Research, 2025)
The implementation of patient safety management is a fundamental component in efforts to improve the quality of healthcare services in hospitals. This study aims to analyze the implementation of patient safety management at Patut Patuh Patju Hospital and to identify the supporting and inhibiting factors in its application. A qualitative research approach was employed, using in-depth interviews with the head manager, head of security, and medical personnel directly involved in patient care. The findings reveal that patient safety principles have been applied through risk identification, the implementation of double-check procedures, and the provision of adequate facilities and infrastructure. However, limitations in human resources, insufficient facilities, and a lack of routine evaluation remain major challenges. A strong culture of patient safety, interprofessional collaboration, and continuous training were found to play significant roles in preventing incidents and improving service quality. In conclusion, a comprehensive and sustainable implementation of patient safety management plays a strategic role in creating a safe working environment, increasing public trust, and supporting the achievement of high-quality healthcare services.